Throughput Improvement of RIPEMD-160 Design using Unfolding Transformation Technique - Shamsiah, Suhaili; Takahiro, Watanabe; Norhuzaimin, Julai (2022)
RIPEMD-160 hash functions are widely used in many applications of cryptography such as digital signature, Hash Message Authentication Code (HMAC) and other data security application. There are three proposed RIPEMD-160 design namely RIPEMD-160 iterative design, RIPEMD-160 unfolding with factor two and RIPEMD-160 unfolding design with factor four. These techniques were applied to RIPEMD-160 designs to examine the inner structure of RIPEMD-160 in terms of area, maximum frequency and throughput of the design. In this project, RIPEMD-160 hash function using unfolding transformation technique with factor four provided high throughput implementation. The throughput of the RIPEMD-160 unfolding design increase significantly. The objective of this project is to enhance the performance of RIPEMD-160 in terms of throughput. By using unfolding transformation factor four technique, the throughput of RIPEMD-160 can be improved which is about 1753.50 Mbps. The percentage of performance to area ratio of RIPEMD-160 unfolding with factor four designs increase 1.51% if compared with RIPEMD-160 design. The results show performance of proposed designs give the highest value compare with other designs. The simulation results were obtained from ModelSim Altera-Quartus II to verify the correctness of the RIPEMD-160 designs in terms of functional and timing simulations.